The influence of agriculture industry characteristics towards management accounting practices (MAPs) - Ali, Fazlin; Repin @ Rebin, Muhamad Fadzil; Thabet, Omer; Zainudin, Zanurul Huzaima; Ismail, Nurain Najwa; Saili, Abdul Rahman (Auricle Global Society of Education and Research, 2024)
The agriculture industry in Malaysia holds a pivotal position, contributing significantly to the nation's GDP and serving as a fundamental source of sustenance through food production. This study explores the influence of the distinctive characteristics of the agriculture industry (perishability of the products, technological advancements, timing in handling the produce, vulnerability, and mechanization); which set it apart from other industries; on the several levels of Management Accounting Practices’s (MAPs) adoption (i.e. for Cost Determination and Financial Control, Provision Of Information for Management Planning and Control, Reduction of Waste in Business Resources and; Creating value through the efficient use of resources) in their organizations. Using descriptive analysis and mean rank comparison, data from 129 agricultural companies are analysed to uncover insights into the relationship between industry characteristics and MAPs adoption. The findings reveal several significant correlations: 1) a positive correlation between the perishability of agricultural products and MAPs adoption; 2) a positive relationship between technology use in agriculture and MAPs adoption; 3) a positive relationship between the vulnerability of agricultural products and MAPs adoption; 4) a positive relationship between timing in handling agricultural products and MAPs adoption; 5) a positive relationship between mechanization in agriculture and MAPs adoption. Furthermore, it is observed that 6) agriculture companies dealing with perishable products, 7) high-tech companies, 8) companies dealing with vulnerable products, 9) companies requiring prompt handling, and 10) highly mechanized companies, tend to implement more advanced management accounting practices. These findings provide valuable insights into how agriculture companies utilize MAPs to optimize profitability, minimize losses, and facilitate effective decision-making, thereby contributing to the sustainable development of the agriculture industry in Malaysia. The study recommends that Malaysian agricultural firms tailor their MAPs to address the unique challenges and requirements of the industry. Continuous monitoring and evaluation of MAPs effectiveness are also emphasized to ensure sustained efficiency and competitiveness.